No change in avilamycin (Surmax® Premix) minimum inhibitory concentration for Clostridium perfringens isolates recovered from poultry up to 7 years post-approval in Canada. (30th March 2023) - Simjee, Shabbir; Gould, George; Maduro, Lila; Boulianne, Martine; Pridmore, Andrew; Parent, Eric
Abstract: Background: Clostridium perfringens, the causative agent of necrotic enteritis (NE) in chickens, has an enormous economic impact on global broiler production. The non-medically important antibiotic avilamycin was approved in Canada in 2014 to prevent and control NE in broiler chickens. Objectives: To compare avilamycin susceptibility in C. perfringens isolates collected pre- and 7 years post-avilamycin approval in Canada and determine the avilamycin resistance mutation frequency rate in C. perfringens . Methods: The MICs of avilamycin were determined for 89 strains of C. perfringens recovered from clinically relevant NE field cases pre-avilamycin approval between 2003 and 2013 ( n  = 50) and post-avilamycin approval between 2014 and 2021 ( n  = 39) across Canada. For determining the mutant prevention concentration (MPC) of avilamycin for C. perfringens strains, a strain with avilamycin MIC of 1 mg/L was randomly selected. Results: MIC studies showed no difference in avilamycin susceptibility in pre-avilamycin and post-avilamycin isolates (MIC50/90 : pre-avilamycin approval 2/2 mg/L and post-avilamycin approval 1/2 mg/L). The MPC was 8 × MIC (8 mg/L) for the selected strain. Conclusions: These findings suggest that the susceptibility of C. perfringens strains to avilamycin was not impacted by its continued use in the 7 years following its approval in Canada. Avilamycin, a non-medically important antibiotic, poses no threat to human health regarding cross-resistance or co-selection of other medically important antibiotics. These factors make avilamycin an appropriate choice for continued use in broiler chickens to prevent and control NE without increased antimicrobial resistance concerns.